Best practices of waqf: Experiences of Malaysia and Saudi Arabia - Md Saad, Norma; Kassim, Salina; Hamid, Zarinah (Universitas Islam Indonesia, 2016)
The main focus of this paper is to examine the best practices of selected waqaf entities in Malaysia and Saudi Arabia. The waqaf entities involved in this study include two corporate waqaf institutions namely Kumpulan Waqaf An-Nur Berhad and IIUM Endowment Fund and five waqaf entities under Islamic Development Bank in Saudi Arabia.This study analyses projects and programs undertaken by these selected waqf entites to achieve their respective objectives.Â Such a comparison is necessary considering the diverse experiences of these selected waqaf entities in view of the differences in their endowments and different corporate management models. The paper concludes that these waqaf entities have adopted an innovative approach developing waqf programs and experimenting new ways of managing and investing waqaf assets. They have created opportunities for the improvement of waqaf institutions and revitalize the potentials of these waqaf assets to yield greater benefits to the society.